Kolekcja Profesora Gimnastyki. - De Luyck, Philippe; Oosterlynck, Baudouin; Renwart, Marc; Wodek (Jette : Atelier 340 Muzeum, 1989)
Ben ; Beuys, Joseph ; Van Severen, Dan ; Boulanger, Michel ; Ile du Timor ; Coeckelberghs, Luc ; Copers, Leo ; De Luyck, Philippe ; Decoster, Jean ; Gees, Paul ; Hamelryck, Ado ; Lybeer, Leen ; Massart, Jean-Georges ; Mesmaeker, Jacqueline ; Schmetz, Francis ; Lacroix, Roger ; Gaube, Bernard ; Dasseville Lunin, Natalia ; Dodeigne, Eugène ; Jacques, Philippe ; Vercheval, Georges ; Lampecco, Antonio ; Eerdekens, Fred ; Rombouts, Guy ; Stuyven, Jef ; Piron, Luc ; Wassenberg, Maio ; Joostens, Paul ; Lizene, Jacques
Nederlands & Frans
Kolekcja Profesora Gimnastyki, Atelier 340 Muzeum, Jette, 12.2 - 12.3. 1989
boek